2015
DOI: 10.1111/1742-6723.12455
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and interrater reliability of paediatric emergency department triage

Abstract: Our findings demonstrate inconsistencies in the accuracy and reliability in which sick children presenting to EDs receive triage scores both within and across hospitals. These results suggest the need for improvements either in current triage nurse training or training resources. Use of the ETEK alone has not resulted in high levels of paediatric triage accuracy or reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 10 publications
2
19
0
Order By: Relevance
“…Inter-rater reliability in the use of POPS lies within the same range as studies such as Jordi et al 10 and rates higher than in the studies such as Allen et al 11 An absolute value at which inter-rater reliability confers a gold standard reliability does not exist; therefore, favourable comparison with other studies is an encouraging finding.…”
Section: Discussionsupporting
confidence: 51%
“…Inter-rater reliability in the use of POPS lies within the same range as studies such as Jordi et al 10 and rates higher than in the studies such as Allen et al 11 An absolute value at which inter-rater reliability confers a gold standard reliability does not exist; therefore, favourable comparison with other studies is an encouraging finding.…”
Section: Discussionsupporting
confidence: 51%
“…We read with interest the recent paper by Allen et al on the accuracy and interrater reliability of paediatric ED triage. 1 The authors suggest that despite significant efforts to improve triage reliability through the national roll-out of the Emergency Triage Education Kit (ETEK), 'the triage category assigned to any given child could differ depending on which nurse conducts the triage assessment and to which hospital they present.' 1 Interestingly, a literature review in 2011 demonstrated that the ATS is valid and reliable for the most acute categories (ATS 1 and ATS 2).…”
Section: Dear Editormentioning
confidence: 99%
“…Triage is defined as prioritizing or sorting the patients for the care and treatment that is due to shortage of the necessary resources in the emergency department (ED) [ 1 ]. Several studies have focused on the validity and reliability of triage scales [ 2 , 3 ] and assessed agreement between nurses and physicians [ 4 , 5 ]. Factors which affect triage practice were also studied [ 6 ].…”
Section: Introductionmentioning
confidence: 99%